Pre-screen projection: from concept to testing of a new interaction technique. - Hix, Deborah.; Templeman, James N.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
Pre-screen projection is a new interaction technique that allows a user to pan and zoom integrally through a scene simply by moving his or her head relative to the screen. The underlying concept is based on real world visual perception, namely, the fact that a person's view changes as the head moves. Pre-screen projection tracks a user's head in three dimensions and alters the display on the screen relative to head position, giving a natural perspective effect in response to a user's head movements. Specifically, projection of a virtual scene is calculated as if the scene were in front of the screen. As a result, the visible scene displayed on the physical screen expands (zooms) dramatically as a user moves nearer. This is analogous to the real world, where the nearer an object is, the more rapidly it visually expands as a person moves toward it. Further, with pre-screen projection a user can navigate (pan and zoom) around a scene integrally, as one unified activity, rather than performing panning and zooming as separate tasks. This paper describes the technique, the real-world metaphor on which it is conceptually based, issues involved in iterative development of the technique, and our approach to its empirical evaluation in a realistic application testbed.